Konsekuensi psikologis dan sosial-ekonomi kehamilan tak dikehendaki pada remaja - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
Abstract The improvement of sex information sources through various channels has lately increased the knowledge on sex among the youth. This fact has now become the basis of various sex practices which is particularly due to the status of youths which is sensitive towards every external influences. Young people are in a transitional position from childhood to adolescence. The field of reproductive health among the youth is one which is directly influenced by the process Of the change. The extramarital sexual intercourse which has lately been increasingly popular has now become a serious problem. As a consequence, unwanted pregnancies have been an important phenomenon in the life of the youth. The paper describes the above tendency, and discusses the psychological and socioeconomic consequences caused by unwanted pregnancy among the youth. Keywords: pregnancies, psychological, socioeconomic